Reaching a Federal/Provincial Consensus on Home Care - Evelyn Shapiro (HealthcarePapers, 2000)
This commentary agrees with Dr. MacAdam that the time has come to implement a national home-care program based on principles similar to those that underpin the Canada Health Act. It also agrees with the general thrust of the proposed vision. However, it disputes some of the grounds on which Dr. MacAdam's vision is based and offers alternative perspectives on key aspects of home care. It concludes with a discussion of the issues that will influence the prospects of reaching a federal/provincial consensus on a Canadian home-care program.